Minorias dentro de minorias: a (in)especificidade do Estatuto da Pessoa com Deficiência a partir de uma análise da judicialização da tomada de decisão apoiada para as pessoas com mal de Alzheimer. - Sousa, Catarina Cardoso (2022)
Nowadays, people with disabilities receive a differentiated legal framework, which comes from the existence of a protection microsystem formed by: the New York Convention, Federal Constitution, Statute of Persons with Disabilities, Civil Code and other laws. Autonomy, empowerment and biopsychosocial inclusion of people with disabilities are the values that permeate every principle that currently supports this microsystem. Understanding the possible physical, cognitive and sensory limitations that prevent or minimize the free access of people with disabilities to the social environment, it was necessary to create a legal model that will support people with disabilities in the exercise of their rights, mitigating any limitation in this aspect. These measures have as their main scope to allow the inclusion and protagonism of people with disabilities in the plural social and legal relationships that permeate their life in society. In this conception, Supported Decision Making appears as a protective legal instrument made available people with disabilities, so the beneficiary of support is empowered to define the limits, content and extent of this protective measure. However, a problem needs to be faced: The specificities that each person with disabilities presents, within their biopsychosocial context and the feasibility of Supported Decision Making as a protective legal instrument made available to people with disabilities for the full exercise of the acts of their lives civil.